ANALISIS PENDAPATAN DAN KESEJAHTERAAN PETANI KARET DI KECAMATAN MUARA BULIAN KABUPATEN BATANGHARI - Nainggolan, Saidin; Effran, Endy; Safitri, Nadia (Program Studi Agribisnis bekerja sama dengan PERHEPI, 2023)
The objectives of this study are: 1) to find out the picture of rubber farming in Muara Bulian District, Batanghari Regency, 2) to find out the income and welfare of rubber farmers in Muara Bulian District, Batanghari Regency and 3) to analyze the relationship between income and welfare of rubber farmers in Muara Bulian District, Batanghari Regency. This study uses a random sampling method. The sampling technique uses the Slovin formula from Taro Yamanae. The sample size is 83 farmers. The results of this study show that: 1) Rubber plants are one of the commodities cultivated in Muara Bulian District, Batanghari Regency. This research was conducted on farmers who are owners as well as cultivators. The average land area owned is 1-3 ha with an average plant lifespan of 20 years. 2) the average income of rubber farmers in Muara Bulian District is Rp. 21,711,783/year, and the average monthly income is Rp. 1,809,315/month. based on BPS criteria from 8 welfare indicators is included in the good category, namely 59 farmers or 71.08%. 3) Based on the results of the Chi square test, it was obtained that the relationship between income and the level of welfare of rubber farmers, the relationship between the two variables was significantly associated, namely X2calculate = 9.275 and X2table = (a=5%, df=1)=3.84, then the value of X2calculate > X2table then accept H1, which means that there is a relationship of income to the level of welfare of rubber farmers in Muara Bulian District, Batanghari Regency